A Conceptual Model on the Relatiionships between Business Strategy, Business Model Innovation, Resource Configuration and Performance - Avanti Fontana, Siti Yasmina Zubaedah (ITB, 2012)
The main objective of this study is to develop a research framwork for strategic maagement researchers to develop sound strategic business model innovation that has practical implication on how to innovate frames' business models. the research identifies factors attributing to effective business model: business strategies, type of business model innovations and types of resource configurations. This study framework can guide leaders and managers to acquire the appropriate capability if coping with business model dynamics as well as major transformation that arises from business model innovations. In addition, the study provides insightful contributions in explaining the influence of business strategies (defender, prospector, analyzer) on business model innovations and firm resource configuration, and their influence on business model effectiveness. this study model is valuable considering the limited amount of empirical work previously done on the topic in question. Based on a case-study research survey in seven companies in Indonesia that took place in 2011-2012, we have drawn first conclusions expressed in four research propositions that deem further tests. One case (Food Co) is highlighted for the description of the study to show some presece and absence of alignment between business strategy, business model innovation, and resource configuration.